A CONNECTION FORMULA FOR THE 2ND PAINLEVE TRANSCENDENT - Clarkson, P; Mcleod, J (Springer-Verlag, 1988)
We consider the second Painlevé transcendent Mathematical expressionIt is known that if y(x) ∼ k Ai (x) as x → + ∞, where -1